High-dose chemotherapy of germ-cell tumors - is it the end of the road? - Szczylik, Cezary; Żołnierek, Jakub; Leśniewski-Kmak, Krzysztof; Langiewicz, Przemysław; Sarosiek, Tomasz; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
High dose chemotherapy supported with autologous bone marrow (BM) or peripheral blood stem cells transplantation (PBSCT) is becoming an increasingly considered option for salvage treatment in patients with disease resistant to platinium-based chemotherapy regimens or recurrent germ cell tumours (GCT). According to published data coming from retrospective matched-pair analyses or phase I-II clinical trials such approach can produce approximately 26-57% of durable complete responses. It is a strong promise of certain progress that is going to be achieved in the closest future as we are able to cure only about 25% of such patients with standard-dose salvage chemotherapy schedules. The next emerging problem is the treatment of so-called poor prognosis patients who are suffering from non-seminomatous GCT with: mediastinal primary tumour location and/or non-pulmonary visceral metastases and/or with defined elevation in b-HCG/AFP/LDH levels. It seems that the introduction of high dose chemotherapy as the first line treatment for this group of patients should result in a 20% increase of cure-rate, when compared to the standard treatment. Although these conclusions can already be drawn from phases II trials, there is a strong need to support them with randomised multi-center phase III clinical trials. However, to date, the phase-III clinical trials had failed to confirm the superiority of high-dose chemotherapy - neither in the salvage nor in the first line treatment. Why is it so? While taking IT-94 under consideration one can risk the hypothesis that it is due to rather small differences in dose-levels and -intensity of cytotoxic agents between arms of the trial, therefore much longer follow-up periods are needed to show benefits coming from such treatment approach. So where is the place of high dose chemotherapy followed by autologous bone marrow/peripheral blood stem cell transplantation in the contemporary treatment of germ cell tumours? What are potential options for future coming? These are questions, authors of this review article are trying to answer by analysing the published clinical data - from the first experiments in early seventies, till the recently completed randomised international phase III study IT-94. The authors' own experience - results of HDC treatment in fifteen patients with poor-prognosing GCT is revealed as well.